"A Community of People Worthy of the Name Community": The Engagement Practices, Wellness, and Self-Identity of Anishinaabe Young Women and Young Two-Spirit People of Eabametoong First Nation - Kirton, Samantha (University of Guelph, 2020)
This thesis explores the relationship between engagement, well-being, and self-identity for Anishinaabe young women and young two-spirit people living in Eabametoong First Nation (EFN). Guided by Community-Based Participatory Research and Indigenous Research Methodologies, I collaborated with contributors from EFN to understand the way engagement, well-being, and self-identity are interconnected. The contributors with whom I spoke contribute to the well-being of their community, and their engagement strengthens their self-identities and becomes a part of their well-being practices. Based on my analysis of interview, participant observation, and photovoice data, I argue that the contributors’ engagement activities are equally as important for maintaining well-being and strengthening self-identity, as well-being and self-identity are for inspiring engagement. Additionally, although contributors do not always see themselves as leaders, all of those with whom I spoke are using their skills and knowledge to serve their community in a way that is characteristic of Indigenous leadership practices.